2011
DOI: 10.2460/ajvr.72.6.780
|View full text |Cite
|
Sign up to set email alerts
|

Impact of successive freezing-thawing cycles on 3-T magnetic resonance images of the digits of isolated equine limbs

Abstract: Although overall image quality was considered unchanged except for the hoof capsule, results suggested that changes induced in cadaver limbs following freezing and thawing, which are probably attributable both to modified and inhomogeneous temperature distribution and direct tissue damage, may alter the reliability of signal intensity in ex vivo MR examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
1
14
1
Order By: Relevance
“…During the arthroscopic procedure a moderate amount of gas was inadvertently but unavoidably introduced into the joint space creating magnetic susceptibility artifacts in the subsequent imaging studies and thus the interpretation of the images was made more difficult compared to the more normal clinical circumstances since some of these gas bubbles may be located adjacent to the artificially created defects and therefore obscuring them. Considering the ex vivo nature of this study and that after collection, all specimens were frozen for a variable period prior to imaging, it is possible that postmortem change and freeze–thaw effects could have led to worsening of artifacts identified on cross‐sectional imaging studies . These artifacts include decrease contrast between different tissues when temperature is around 0°C or a central signal reduction artefact, resembling an isotherm distribution .…”
Section: Discussionmentioning
confidence: 99%
“…During the arthroscopic procedure a moderate amount of gas was inadvertently but unavoidably introduced into the joint space creating magnetic susceptibility artifacts in the subsequent imaging studies and thus the interpretation of the images was made more difficult compared to the more normal clinical circumstances since some of these gas bubbles may be located adjacent to the artificially created defects and therefore obscuring them. Considering the ex vivo nature of this study and that after collection, all specimens were frozen for a variable period prior to imaging, it is possible that postmortem change and freeze–thaw effects could have led to worsening of artifacts identified on cross‐sectional imaging studies . These artifacts include decrease contrast between different tissues when temperature is around 0°C or a central signal reduction artefact, resembling an isotherm distribution .…”
Section: Discussionmentioning
confidence: 99%
“…Similar equine research studies described severe changes in MR image quality of soft tissues after freezing [16]. To prove, whether the image quality suffered in post-mortem or frozen-thawed soft tissues in the current study, the image quality and visibility of the pulp, PDL, mucosa of the sinuses and infra-orbital canal’s soft tissue were additionally evaluated in group B and C.…”
Section: Discussionmentioning
confidence: 77%
“…Most of these research examinations have been performed with cadaveric heads and some imaging procedures are performed on frozen and thawed heads. A decrease of the magnetic resonance (MR) signal was described for equine limbs when evaluating defined structures immediately post-mortem and frozen-thawed [16]. Regarding equine dental imaging, there is currently a lack of information about whether the image quality suffers in equine heads post-mortem or frozen-thawed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most likely, no abnormalities were present at the level of the bone at the place of contact during induced hyperextension as MRI has a high sensitivity for the detection of abnormalities at the level of subchondral bone such as bone sclerosis or bone bruise (Smith et al., ). However, it is possible that post‐mortem changes and freeze–thaw effects could have an effect on the MR images as freezing–thawing processes can induce changes of the signal‐to‐noise ratio in images and may alter the reliability of signal intensity in ex vivo MRI examinations (Bolen et al., ). In contrast, it has been reported that there is no subjective difference between images of the same digits obtained before death and after post‐mortem freezing and thawing (Murray et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…If radiographic abnormalities were detected at the level of one of the MCP/MTP joints of a horse, that horse was excluded from the study and new specimens were collected until a total of 20 normal joints originating from five horses were collected. Before the MRI examination, limbs were thawed at ambient temperature for 24 h. It has been proven that this procedure has the least influence on image quality (Bolen et al., ).…”
Section: Methodsmentioning
confidence: 99%